SUPPLY CHAIN PERFORMANCE MEASUREMENT OF DOWNSTREAM WOODWORKING INDUSTRY - Natalia Hartanto; Muhammad Asrol; Muhammad Noor Badruddin (JARES (Journal of Academic Research and Sciences), 2023)
People’s needs of wood toward increase. Along with the development of technology, the woodworking industry exists to balance the fulfilment of human needs of wood and to increase the value added of timber forest resources. The objective of this study is to identify the supply chain configuration and to measure the supply chain performance of the downstream woodworking industry. Metrics validation using the supply chain operation reference (SCOR) framework that is adjust to industry activities through discussions with stakeholders. Performance metrics are weighted using the Analytical Hierarchy Process (AHP). The result of the supply chain performance measurement of the downstream woodworking industry obtains a value 76.21 in the good category indicating that XYZ has achieved the target of 59%. 41% need to improve performance, namely 32% in the Average category, 5% in the Marginal category, and 4% in the Poor category.